Digital Transformation of Sharia Finance: Challenges of Harmonizing Regulations and Fatwas in the Application of Artificial Intelligence in Sharia Fintech Financing in Indonesia - Herlambang, Herlambang; Wahyudi, Amin (Jurnal Iqtisaduna, 2025)
The digital transformation of Islamic finance has brought significant changes, particularly through the adoption of Artificial Intelligence (AI) in financing services. This innovation not only enhances efficiency but also introduces new challenges in legal, ethical, and Sharia compliance aspects. This study aims to analyze the relationship between national financial regulations and Sharia fatwas in governing the use of AI in Islamic financing. Using a qualitative and descriptive-normative approach, this research examines the roles of the Financial Services Authority (OJK), Bank Indonesia (BI), and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in maintaining a balance between digital innovation and the principles of maqashid Syariah. The findings indicate that the harmonization of regulations and fatwas is crucial to the success of digital transformation in Islamic finance. Institutional collaboration, strengthening of Sharia digital literacy, and the development of adaptive fatwas toward emerging technologies are strategic efforts to ensure that AI implementation aligns with the values of justice and public benefit in Islam.